2019
DOI: 10.1016/j.buildenv.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of a compact embedded photometric device for real-time daylighting computing in office buildings

Abstract: Studies have shown that the exposure to daylight can have substantial visual/non-visual benefits for building occupants. To optimise daylighting provision while maintaining a comfortable visual environment, daylighting control systems have been investigated by architectural design and academic research for a number of years. However, real-time regulation of daylighting in buildings requires transient daylighting simulation with high accuracy and, daylighting simulation, as performed to date, is significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The design of the automated EC glazing integrates an embed-ded photometric device (EPD) [41] that is attached on the glass, with its imaging system targeted towards outdoors as illustrated in Figure 1, to control glazing tints to improve visual comfort for occupants, as a standalone system. The EPD acts as both a sensing unit and a controller for the EC glazing.…”
Section: Systematic Design Of the Automated Ec Glazingmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of the automated EC glazing integrates an embed-ded photometric device (EPD) [41] that is attached on the glass, with its imaging system targeted towards outdoors as illustrated in Figure 1, to control glazing tints to improve visual comfort for occupants, as a standalone system. The EPD acts as both a sensing unit and a controller for the EC glazing.…”
Section: Systematic Design Of the Automated Ec Glazingmentioning
confidence: 99%
“…The EPD, proposed and demonstrated by Wu et al [41,42], mainly comprises a low-cost image sensor, lens, and a field pro-grammable gate array (FPGA) processor. The imaging system of the EPD was deliberately calibrated in the spectral response, vignette effect, signal response curves, and geometric mapping.…”
Section: Embedded Photometric Devicementioning
confidence: 99%
See 1 more Smart Citation
“…Second, the camera spectral responsivity does not necessarily align with the sRGB responsivity. For instance, Wu et al indicated that the spectral responsivity of the camera can have severe disparity with the RGB colour space as manufacturers aim to achieve compelling colours (Wu et al, 2019). As a result, different cameras, with different spectral responsivities, might have varying capabilities in terms of luminance distribution measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Wu et al . 18 indicate that the spectral responsivity of the camera can have a severe disparity with the RGB colour space as manufacturers aim to achieve compelling colours. The sRGB colour space is a rendered or output-referred colour space designed for an output medium, 11,17 while HDR images are scene-referred images because the pixels are directly related to the radiance of the captured scene 11 .…”
Section: Introductionmentioning
confidence: 99%